Effects of consuming date fruits (Phoenix dactylifera Linn) on gestation, labor, and delivery: An updated systematic review and meta-analysis of clinical trials. (August 2019) - Nasiri, Morteza; Gheibi, Zeinab; Miri, Ali; Rahmani, Jamal; Asadi, Masoumeh; Sadeghi, Omid; Maleki, Vahid; Khodadost, Mahmoud
Highlights: Date fruits consumption significantly reduces gestation duration. Date fruits consumption significantly increases cervical dilation on admission. Date fruits consumption significantly shortens duration of the 1st stage of labor. Date fruits consumption significantly reduces duration of the 2nd stage of labor. Abstract: Background: Recent studies have shown that consumption of date fruits during pregnancy and also postpartum period might affect some pregnancy outcomes. We performed an updated systematic review and meta-analysis about the effects of consuming date fruits on gestation, labor, and delivery. Methods: Two researchers independently searched the online databases of PubMed, Scopus, Web of Science, Embase, Google Scholar, and EBSCO up to January 2019 for clinical trials examining the effects of date fruits consumption on any types of gestation, labor, and delivery outcomes. A fixed-effects model or random-effects models were applied to pool data, where appropriate. Quality assessment was done by Jadad scale. Results: In total, 11 and 8 studies were included in the systematic review and meta-analysis. Meta-analysis revealed that date fruit consumption significantly reduced gestation duration (pooled effect size: −0.30, 95% CI: −0.45, −0.15; P < 0.001), increased cervical dilation on admission (pooled effect size: 0.94, 95% CI: 0.88, 1.00; P < 0.001), and shorten duration of first stage of labor (pooled effect size: −50.09, 95% CI: −72.25, −27.93; P < 0.001). Also, it was revealed that date fruit consumption significantly reduced duration of second stage of labor in fixed-effects model (pooled effect size: −9.85, 95% CI: −14.00, −5.70; P < 0.001); however, this effect was not significant in random-effects analysis (pooled effect size: −11.27, 95% CI: −28.23, −5.68; P = 0.193). Conclusions: Date fruits intake seems to reduce gestation duration and duration of the first stage of labor, and also increase cervical dilation on admission.